Cardiac arrest: a rare complication of pallid syncope?. Issue 815 (September 1993) - Taiwo, B.; Hamilton, A. H.
Abstract : Cardiac arrest is rare in children. Breath-holding, on the other hand, is fairly common. We report a case in which one complicated the other with serious consequences. A review of the literature on the subject was undertaken.